DEVELOPING SCIENTIFIC ATTITUDE AND RESPONSIBILITY IN WRITING THE FINAL THESIS THROUGH GUIDED WRITING AS A MODEL OF GUIDANCE - Dwiyanto Djoko Pranowo (International Conference on Languages and Arts, 2014)
This acticle is based on research result that aimed to develop a writing thesis model using guided writing technique for the students who are constructing the final task. The development of this model is motivated by the length of the final project completion experienced by most students majoring in French Education. Many students have difficulties in developing a paragraph so that they do cut corners by compiling existing literature illegally. This has implications for the duration of the study period as well as the originality of student papers that still must always be questioned.  This research was designed to 1) literacy study related to the tehnique of developing paragraph and writing scientific paper, 2) create a prototype model of the writing guidance by utilizing guided writing, and 3) Test the effectiveness of the model.  The first year targeted research is a model development and try out the model. In the second year research is the test of effectiveness and the writing of guidance manual. The first stage uses descriptive method in exploratory studies, and focus group discussion (FGD) for preparing the prototype of models. The research design is research and development. The second stage uses experimental models to test the effectiveness and workshops for the preparation of a guidance model book based on guided writing. The results of the phase I study were 1) models of the guidance steps in writing the final task (thesis), and 2) the student worksheet consisting of a) Framework baseline, b) framework of chapter I, c) the framework of chapter II, d) the framework of chapter III, E) framework proposal research, f) research result framework. From the try out of the model to the 12 students who were writing thesis, there were 4 students who completed their thesis successfully in an average time of 6.5 months. The two students were ready to the final exams, and the rest was on going supervision.   Keywords: guided writing, guidance model, scientific attitude, responsibility attitude, guided Writing